Cross-Disciplinary Lessons in an Elementary Public Institution - Josefina Quintero; Diana Yurany Álvarez; Andrea Arcila (Universidad Nacional de Colombia, 2021)
This article reports the results of an action-research study, carried out in the fourth grade of a Colombian public elementary school, which sought the integration of the teaching of English and the natural sciences through cross-disciplinary lessons that followed the principles of content-based instruction. Observation, action plan, and evaluation were the ongoing research stages. Interviews, workshops, and the students' portfolio were the main instruments used to collect data. Results revealed that the cross-disciplinary lessons were appropriate and useful to connect the foreign language learning with other school subjects. Beginner students of English demonstrated an enhancement in the communicative skills and developed contextualized learning strategies, which proved the importance of integrating English with scientific contents as a contribution to curriculum innovations.